Comparative genomic analysis of uropathogenic Escherichia coli strains from women with recurrent urinary tract infection - Flores-Oropeza, Marco A.; Ochoa, Sara A.; Cruz-Córdova, Ariadnna; Chavez-Tepecano, Rolando; Martínez-Peñafiel, Eva; Rembao-Bojórquez, Daniel; Zavala-Vega, Sergio; Hernández-Castro, Rigoberto; Flores-Encarnacion, Marcos; Arellano-Galindo, José; Vélez, Daniel; Xicohtencatl-Cortes, Juan (Frontiers in Microbiology, 2024)
Introduction. Recurrent urinary tract infections (RUTIs) caused by uropathogenic Escherichia coli are costly public health problems impacting patients´ quality of life. Aim. In this work, a comparative genomics analysis of three clinical RUTI strains isolated from bladder biopsy specimens was performed. Material and Methods. 172 whole genomes of urinary tract E. coli strains were selected from the NCBI database. The search for virulence factors, fitness genes, interest regions, and genetic elements associated with resistance was manually carried out. The phenotypic characterization of antibiotic resistance, haemolysis, motility, and biofilm formation was performed. Moreover, adhesion and invasion assays with human bladder HTB-5 cells, and transmission electron microscopy (TEM) were performed. Results. The UTI-1_7744U and UTI-3_455U/ST1193 strains were associated with the extraintestinal pathotypes, and the UTI-2_245U/ST295 strain was associated with the intestinal pathotype, according to a phylogenetic analysis of 172 E. coli urinary strains. The three RUTI strains were of clinical, epidemiological, and zoonotic relevance. Several resistance genes were found within the plasmids of these strains, and a multidrug resistance phenotype was revealed. Others virulence genes associated with CFT073 were not identified in the three RUTI strains (genes for type 1 and P fimbriae, haemolysin hlyA and sat toxin). Quantitative adhesion analysis showed that UTI-1_774U, was significantly (p < 0.0001) more adherent to human bladder HTB-5 cells. Quantitative invasion analysis showed that UTI-2_245U was significantly more invasive than the control strains. No haemolysis or biofilm activity was detected in the three RUTI strains. The TEM micrographs showed the presence of short and thin fimbriae only in the UTI-2_245U strain. Discussion. The high variability and genetic diversity of the RUTI strains indicate that are a mosaic of virulence, resistance, and fitness genes that could promote recurrence in susceptible patients.